Pathogenetic Substantiation of the Usability of the Natural Anticoagulant Sulodexide in a Combine Treatment of Pregnant Women with Premature Delivery - T. A. Mielikova (Kazimierz Wielki University, 2017)
Clinical effectiveness of the Natural Anticoagulant Sulodexide at violations in system of a hemostasis at pregnant women with threat of premature births is studied. 57 pregnant women with threat of premature births are examined. At 31 women in a combine of treatment applied Sulodexide, at 26 - a heparin, at 20 the physiological current of a gestation is noted. Conducted all-clinical examination of pregnant women, estimated a condition of system of a hemostasis before combine treatment. At patients at threat of premature births essential have significant changes in the hemostatic system, manifested in thrombocyte hyper-aggregation and hyper-coagulation in the plasma link of hemostasis, as well as appearance of markers of activating the intravascular blood coagulation. Use of the natural anticoagulant sulodexide for pregnant women provided the high antithrombotic potential  and moderate anti-coagulative activity, contributed to normalization of rheological behavior of blood by influence on all links of a hemostasis, to improvement of the course of the gestational period and the functional state of the fetus.